PENGARUH CITRA MEREK, KEPERCAYAAN MEREK DAN KESADARAN MEREK TERHADAP LOYALITAS MEREK TEH BOTOL SOSRO - Simangunsong, Elisabeth; Bangun, Kristina (Jurnal Manajemen dan Bisnis, 2024)
This study aims to evaluate the partial and simultaneous effects of brand image, brand trust, and brand awareness on brand loyalty for "The Botol Sosro" using a sample of 96 respondents. Data were collected through questionnaires and documentation, and analyzed using multiple linear regression. The research findings indicate that brand image (CM), brand trust (KM), and brand awareness (KesM) have a positive impact on brand loyalty for "The Botol Sosro". Brand trust holds a more significant influence compared to other variables. The t-test results show that CM = 2.236 with a significance of 0.028, KM = 2.675 with a significance of 0.009, and KesM = 2.110 with a significance of 0.038. With a 5% margin of error, Ho is rejected, and H1 is accepted, indicating that all three variables significantly and positively influence brand loyalty. The F-test reveals an F value of 25.407 with a significance of 0.000, confirming that collectively, brand image, brand trust, and brand awareness have a positive and significant impact on the loyalty of Botol Sosro tea. The correlation coefficient (r) of 0.818 indicates a very strong relationship between brand loyalty and brand image, brand trust, and brand awareness. The coefficient of determination (r2) of 0.669 signifies that these three independent variables can explain 66.9% of the variation in brand loyalty, leaving 33.1% explained by other factors. To strengthen brand image, brand trust, and brand awareness, consistency in visual elements and brand messaging across all communication channels is crucial. Building consumer trust through transparency, consistent communication, and ensuring that products or services meet or exceed expectations will enhance a positive reputation and customer trust.